Comparative transcriptomic response of two Pinus species to infection with the pine wood nematode Bursaphelenchus xylophilus - Gaspar, Daniel (2020)
Pine wilt disease (PWD) caused by pine wood nematode (PWN), Bursaphelenchus xylophilus, is a serious threat to global forest populations of conifers, in particular Pinus spp. Recently, the presence of PWN was reported in dead Yunnan pine (Pinus yunnanensis) trees under natural conditions. To further understand the potential impact caused by PWN in Yunnan pine populations, a transcriptional profiling analysis was performed over di erent time points (0 hours (h), 6 h, 24 h, 48 h, and 7 days) after PWN inoculation. A total of 9961 di erentially expressed genes were identified after inoculation, which suggested a dynamic response against the pathogen, with a more intense pattern at 48 h after inoculation. The results also highlighted a set of biological mechanisms triggered after inoculation that provide valuable information regarding the response of Yunnan pine to PWN infection. When compared with maritime pine (Pinus pinaster), the Yunnan pine response was less complex and involved a smaller number of di erentially expressed genes, which may be associated with the increased degree of resistance to PWN displayed by Yunnan pine. These results revealed di erent strategies to cope with PWN infection by these two pine species, which display contrasting degrees of susceptibility, especially in the timely perception of the infection and response magnitude